Improved theoretical model of InN optical properties. Issue 3 (17th February 2014) - Ferreira da Silva, A.; Chubaci, J. F. D.; Matsuoka, M.; Freitas, J. A.; Tischler, J. G.; Baldissera, G.; Persson, C.
Abstract: The optical properties of InN are investigated theoretically by employing the projector augmented wave (PAW) method within Green's function and the screened Coulomb interaction approximation (GWo ). The calculated results are compared to previously reported calculations which use local density approximation combined with the scissors‐operator approximation. The results of the present calculation are compared with reported values of the InN bandgap and with low temperature near infrared luminescence measurements of InN films deposited by a modified Ion Beam Assisted Deposition technique. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)